Análise das ações preventivas executadas pelo DETRAN/AM e imtrans na cidade de Manaus durante o carnaval dos anos de 2007 e 2008: um estudo de caso - Silva, José Militão Rodrigues da (2008)
Currently, the traffic accidents if have constituted as a serious partner-economic problem and of public health, being responsible for 1,2 million deaths and 50 million wounded, per year in everybody. Many are the causes that generate these accidents. Brazil is had as one of the worldwide leaders in traffic accidents has 30 years more than. The cost of these traffic accidents is very raised. Manaus, is a city of the Region North, considered regional polar region, she is one of the 49 urban agglomerations of the country, and presents a population of 1.688.524 inhabitants approximately. As the majority of the Brazilian cities, the urban transit is violent, time that presents one high index of traffic accidents. During the years of 2007 and 2008, the State Department of Transit of Amazon (Detran/AM), it placed in functioning the educative program of prevention of called traffic accidents 'Solidary Hitchhiking', known popularly as 'Disk Pileque'. This work consisted of analyzing the injunctions taken the effect during the carnavalescos periods of 2007 and 2008, with the execution of the solidary hitchhiking, demonstrating its effectiveness in the reduction of traffic accidents with fatal victims. The execution of the program if gave through the proper Detran, that mounted project in the direction to provide attendance better to the citizen. The data had been gotten through reports emitted for the Detran/AM, of luck that showed the related specificities to the accidents. The results had shown that the execution of the program was positive, therefore, the number of done requests surpassed the expectations mainly, generating with this reduction of costs and reduction of the amount of fatal victims in the city for occasion of the analyzed periods. It was suggested that the program is executed in other periods of the year.